2017
DOI: 10.5604/01.3001.0010.7851
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of children suffering from motor disabilities as evaluated by their parents

Abstract: Purpose: We assessed the quality of life of children with motor disabilities in comparison with healthy children, as evaluated by their parents, using the CHQ-PF28 questionnaire (Child Health Questionnaire—Parent Form). Materials and methods: In a prospective study, we evaluated the quality of life of 105 children with motor disabilities. Results: Our research showed lower quality of life in the group of children with motor disabilities compared with controls, both in terms of physical and psychosocial health.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
3
3
0
1
Order By: Relevance
“…Results for each dimension were compared to the Hungarian reference data (The Kidscreen Group Europe, 2016) and mean T-values of the subsamples by dimensions were also compared with ANOVA. The results of this QOL assessment partially confirm the results of other research in this field, thereby indicating that the QOL of children and youth with disabilities is lower than that of their peers with TD (Sabaz et al, 2001, Calley et al, 2012De Vries & Geurts, 2015;Clark et al, 2015;Biggs & Carter, 2016;Wojtkowski et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Results for each dimension were compared to the Hungarian reference data (The Kidscreen Group Europe, 2016) and mean T-values of the subsamples by dimensions were also compared with ANOVA. The results of this QOL assessment partially confirm the results of other research in this field, thereby indicating that the QOL of children and youth with disabilities is lower than that of their peers with TD (Sabaz et al, 2001, Calley et al, 2012De Vries & Geurts, 2015;Clark et al, 2015;Biggs & Carter, 2016;Wojtkowski et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…The research found greater QOL of children with TD in the domains of functioning, and participation and physical health. Lower levels of QOL of children with PD were found by Wojtkowski et al (2017) as well. The parent questionnaires detected lower QOL of children with motor disabilities compared to TD controls, both in terms of physical and psychosocial health.…”
Section: The Qol Of Children and Adolescents With Disabilitiesmentioning
confidence: 93%
“…Studies have specified that any of the developmental communication disorders (or speech-language disorders), such as speech impairment [5,6], hearing impairment [5,7] and stut-tering [8] negatively affects the function of the whole family; therefore, family members face many problems. Some of the problems of families in such cases include more anxiety, depression, stress and worries [5,[9][10][11], mental and physical problems [12][13][14], self-isolation and social isolation [13], work problems and resignation [15], and financial issues [16]. Such problems consequently reduce the parents' QoL [7,10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Their focus was on children with specific communication disorders, such as speech impairment, hearing loss, and stuttering. They had a quantitative approach using common questionnaires, including the 36-item short-form health survey (SF-36), the WHO QoL-BREF (WHOQOL-BREF), and the 12-item short-form health survey (SF-12) [1,5,12,15,23,24]. Allik et al [12] investigated parents' QoL of children with autism and Asperger using the SF-12 questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…3 Por otro lado, la calidad de vida de los niños con discapacidades aumentará en gran medida con el ajuste de las condiciones del entorno a sus necesidades. 4 Tomando en consideración lo anterior, los objetivos del artículo son identificar, analizar y sintetizar las perspectivas por parte de países latinoamericanos con respecto a la situación de accesibilidad para niñas, niños y adolescentes que son usuarios de sillas de ruedas, así como realizar una reflexión en el área de Odontología Pediátrica.…”
Section: Introductionunclassified